Physical stimulation by REAC and BMP4/WNT-1 inhibitor synergistically enhance cardiogenic commitment in iPSCs. - Valentina Basoli (PLoS ONE, 2019)
It is currently known that pluripotent stem cells can be committed in vitro to the cardiac lineage by the modulation of specific signaling pathways, but it is also well known that, despite the significant increase in cardiomyocyte yield provided by the currently available conditioned media, the resulting cardiogenic commitment remains a highly variable process. Previous studies provided evidence that radio electric fields asymmetrically conveyed through the Radio Electric Asymmetric Conveyer (REAC) technology are able to commit R1 embryonic stem cells and human adipose derived stem cells toward a cardiac phenotype. The present study aimed at investigating whether the effect of physical stimulation by REAC in combination with specific chemical inductors enhance the cardiogenic potential in human induced pluripotent stem cells (iPSCs). The appearance of a cardiac-like phenotype in iPSCs cultured in the presence of a cardiogenic medium, based upon BMP4 and a WNT-inhibitor, was consistently increased by REAC treatment used only during the early fate differentiation for the first 72 hours. REAC-exposed iPSCs exhibited an upregulation in the expression of specific cardiogenic transcripts and morphologically in the number of beating clusters, as compared to cells cultured in the cardiogenic medium alone. Our results indicate that physical modulation of cellular dynamics provided by the REAC offers an affordable strategy to mimic iPSC cardiac-like fates in the presence of a cardiogenic milieu.